Superwetting and mechanically robust MnO2 nanowire–reduced graphene oxide monolithic aerogels for efficient solar vapor generation. Issue 30 (17th July 2019) - Zhang, Zheng; Mu, Peng; Han, Jingxin; He, Jingxian; Zhu, Zhaoqi; Sun, Hanxue; Liang, Weidong; Li, An
Abstract : Through the method of integrated molding and simple spraying, our PNGA can be easily prepared, which exhibit solar steam generation efficiency of 93.8% under 1 sun and excellent barrier properties for pollutant, thus increase practical possibilities. Abstract : Solar vapor generation based on light-to-heat conversion via photothermal materials has been considered as one of the emerging technologies for utilizing solar energy. Here, we report the fabrication of a novel monolithic aerogel (PNGA) composed of hydrophilic treated MnO2 nanowires and reduced graphene oxide (rGO) followed by in situ coating of polypyrrole on the surface of the PNGA to construct a light-to-heat conversion layer for efficient solar steam generation. Analysis of the morphology and porosity of the PNGA shows that the aerogel is full of interconnected pores and open channels with a low apparent density (0.127 g cm −3 ) and large specific surface area (1142.7 m 2 g −1 ), which endow it with excellent thermal insulation (a low thermal conductivity of 0.21882 W m −1 K −1 in the wet state), self-floating and rapid water transmission properties. Benefiting from the polypyrrole coating, the PNGA shows a superintense optical absorption of ca. 100%. Interestingly, a superhydrophilic wettability could be achieved after surface modification of the PNGA with phytic acid, which could dramatically enhance its water transportation ability. Furthermore, the PNGA maintains a certain mechanical strength (0.08 MPa under 30% strain), thus making it mechanically robust to withstand the harsh environment. Taking the advantages mentioned above, our PNGA possesses an outstanding energy conversion efficiency of 93.8% under 1 kW m –2 irradiation, which is 4.9 times that of pure water (19.1%). In addition to the excellent ionic isolation and dye liquid treatment ability, the PNGA shows excellent stability and its energy conversion efficiency remains nearly unchanged after ten consecutive tests. Based on its excellent mechanical stability and high recyclability and a simple and scalable manufacture process, our PNGA sample may have great potential as an efficient photothermal material for a wide range of large-scale applications such as solar steam generation, wastewater treatment, seawater desalination and so on.